ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN PADA UD MANDIRI KARYA TEKNIK CABANG JEMBER - Yulianto, Teguh Setiawan; Astuti, Diana Dwi; Ningsih, Wiwik Fitria (RISTANSI: Riset Akuntansi, 2024)
This research was conducted to analyze the application of sales accounting information systems at UD.Mandiri Karya Teknik, Jember Branch. This research uses a qualitative method that is descriptive with a case study approach. This study uses in-depth interviews with each informant. The research results show that UD. Mandiri Karya Teknik, Jember Branch has implemented a sales accounting information system that is good but relatively simple. The recording of cash receipts and disbursements has used a system so that managers can make decisions easier. However, the notes received by the admin section tend to be simple with manual writing by marketing. This is an obstacle for admins in scanning reports into books or inputting them into the system.